The superioty of supercritical fluid extraction over steam distillation and solvent extraction methods for the extraction of aroma from Salacca zalacca (Gaernt..)Voss. - Hilmi, Nur Nadhirah; Mat So'ad, Siti Zaiton; Siddiqui, Mohammad Jamshed Ahmad; Sarker, Md. Zaidul Islam; Rahman, Md. Mokhlesur; Juahir, Hafizan; Raja Hussin, Tengku Mohammad Ariff; Wan Nik, Wan Mohd Norsani; Siddique, Md Nurul Islam (Oriental Scientific Publishing Company, 2019)
Salacca zalacca (Gaertn.) Voss (salak fruit or snake fruit) is a species of palm tree native to Southwest Java and North Sumatra in Indonesia. It is known as one of the tropical fruits in Malaysia. It is a reddish-brown scaly skin with pleasant pineapple, pear and banana-like aromas. Its strong pleasant aroma, S. zalacca has high potentiality in the perfumery and pharmaceutical industries. The volatile aromas of plants are usually extracted by conventional extraction methods such as steam distillation and solvent extraction methods. These methods are laborious, have incomplete extraction process, require long extraction time, and produced hazardous chemical wastes. A new extraction technique supercritical fluid extraction (SFE) were introduced in this study to overcome these limitations. It is rapidly gaining attention due to its superior benefits over the conventional extraction methods. In this study, the volatile aromas of S. zalacca were extracted by steam distillation, solvents extraction with hexane, diethyl ether and dichloromethane (DCM), and SFE. Carbon dioxide was used for the supercritical fluid. The efficiency and percentage yield of these aromas were compared. The percentage yields by SFE extracts were observed (10 MPa, 30 °C: 0.2577 %; 25 MPa, 50 °C: 0.2375 %; 40 MPa, 70 °C: 0.2721 %) and then the steam distillation (0.1855 %), diethyl ether (0.5692 %), hexane (0.0511 %) and DCM (0.1358 %) were obtained. However, SFE produced a bit lower yield (40 MPa, 70 °C: 0.2721 %) than the diethyl ether solvent extraction (0.5692 %). Over all, SFE was found to be more efficient, environmentally friendly and a produce a satisfactory amount of extract by this SFE required shorter extraction time and a small amount of sample.